Studi Literatur: Implementasi Metode Pembelajaran Kooperatif Tipe Jigsaw dalam Meningkatkan Motivasi Belajar IPA Siswa SMP - Yuneva Yuneva (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study explores the implementation of the Jigsaw method, a cooperative learning strategy, in a junior high school setting and its impact on student motivation. The aim is to investigate how the Jigsaw method affects students’ motivation to learn, especially in the context of science learning. Active student participation in the learning process is emphasized in the Jigsaw Cooperative Learning Method. A literature review is the research methodology used, with an emphasis on sources released in the last ten years to ensure validity and relevance. Articles, books, dissertations, and research reports discussing the Jigsaw approach and its impact on junior high school students’ motivation are good places to find these sources. The findings indicate that the Jigsaw method significantly increases student engagement and motivation. Students are divided into diverse groups where each member learns a specific section of the material, the Jigsaw method encourages collaboration and peer teaching, which are essential for developing social skills and a sense of responsibility among students. This confirms that the Jigsaw method is a viable strategy for improving student motivation and learning outcomes in a junior high school setting.